Reward Found in Synchronous Teaching English at SMA Muhammadiyah Malang - Sri Hartiningsih; Rahmawati Khadijah Maro; Miftahul Hamim; Royan Jamil Syauqi; Dea Triana Devy (Universitas Muhammadiyah Enrekang, 2023)
To increase teaching learning better, it is needed the students’ involvement in the process of education through giving motivation as the students are lack of confident, afraid to make mistake and shy to communicate in English. The aims of this article are to elaborate rewards and its type found in Synchronous and Asynchronous Teaching English At SMA Muhammadiyah 1 Malang. This research was applied qualitative design as it was to dig out the research problems as the rewards and its kind in teaching English at SMA Muhammadiyah I Malang. The research subjects are two English teachers in SMA Muhammadiyah I Malang while to get data was used focus group discussion and observation. Based on FGD and observation, it was found Good, OK, Amazing, Best answer, Nice answer, Good answer, Best, Excellent, Try again, Nice try, Giving thumb, Giving two thumbs, Giving applause, Smiling, Clapping the shoulder of the students, Money, Book or novel, Score whereas the type found are compliment, gesture, present and combining compliment and gesture and also double compliment as well as double compliment and gesture.